Assistance to Firefighters Program : Distribution of Fire Grant Funding. (U.S. Congressional Research., 2009)
Examines administration of and FY2001-FY2009 funding for the assistance to firefighters program, which provides Federal grants to local fire departments to address equipment, training, and other firefighter-related needs. Reviews distribution trends and guidelines for assistance to firefighters program grants; and addresses issues in the 111th Congress. Includes tables.